Effect of trenches on the habitat of aquatic organisms in a salt marsh in Saga, Japan - Y. Nagahama; K. Nishimura; H. Yamanishi (International Association of Lowland Technology, 2015)
Trenches were constructed to control the growth of Phragmites australis on a riverbank in the Ushizu River in Saga, Japan. However, the effect of these trenches on the habitat of aquatic organisms is unclear. The purpose of this study is to clarify the effect that trenches have on aquatic organisms in the tidal river. The burrow density of a type of sand crab (Ilyoplax deschampsi) and the abundance of aquatic organisms (such as fish and shrimp) in our trenches were measured. The number of I. deschampsi burrows around trench D was similar to that observed before trench construction. However, mud sedimentation was accelerated in shallow trench D’, which created a suitable habitat for this species. Additionally, we found shrimp and gobies in all our trenches. This indicates that artificial trenches do provide habitat for shrimp and gobies in riverside marshes. Moreover, an endangered species and many aquatic insects were collected. Our results suggest that trenches provide important habitats for rare fishes and aquatic insects, similar to that of a lagoon.